Enhancing Business Sustainability through Creativity: The Role of Product Innovation and Entrepreneurial Skills - Jatlan, Nasywa Ramadhanti; Hidayah, Risma Ningsih Nur; Zahidah, Faridah Khazimatun; Adilah, Alya Aryanti; Kumalasari, Rafi'ah (Lentera Ilmu Nusantara, 2025)
This study aims to analyze the effect of product innovation on business sustainability, by considering creativity as a mediating variable and entrepreneurial skills as a moderating variable on fast food MSME actors in Bekasi Regency. The research method used is a quantitative research method. The data source used is primary data by distributing questionnaires online and direct interviews. The population in the study was all fast food MSME actors in Bekasi Regency whose number is unknown. The number of samples in this study was 105 respondents obtained using Purposive sampling and the Hair at,.al formula. The results showed that product innovation did not have a significant direct effect on business sustainability. The data analysis process was carried out by testing the outer model to ensure the validity and reliability of the indicators. Continued with the R Square test and path analysis to evaluate the relationship between constructs, including the mediation effect. The significance of the relationship is determined based on the probability value of the bootstrapping process. However, there is a significant indirect effect through creativity, which means that creativity mediates the relationship. Meanwhile, entrepreneurial skills do not play a significant role in moderating the relationship between product innovation and business sustainability. This research provides novelty by integrating creativity as a mediator and entrepreneurial skills as a moderator in the context of fast food MSMEs, which has been rarely examined in previous studies. The findings also carry practical implications by highlighting the importance for MSME actors to foster creativity in order to achieve business sustainability, even when product innovation alone does not guarantee success.